Injeção de imidacloprido no controle do pulgão-preto-do-coqueiro - Moura, José I. L.; Pereira, Rosane R. da C.; Santos Filho, Lindolfo P.; Santos, Kátia C. B.; Valle, Raul R. M. (Entomological Communications, 2020)
Trunk injection with Imidacloprid to control the palm aphid The injuries caused by the palm aphid, Cerataphis lataniae, on coconut plants may provoke economic losses. Thus, insecticide injection into the tree can provide protection and control against this pest. Our goal was to evaluate the efficiency of injection of imidacloprid on coconut trees to control the palm aphid. The experiment was carried out at the Lemos Maia experimental station, Ceplac, Una, Bahia, Brazil. The treatments applied were: 1) injection of 10 mL of the commercial product Provado® 200 SC (2 g i.a imidacloprid) in the stipe; 2) injection of 20 ml of Provado® 200 SC diluted in water (1 g i.a imidacloprid) and; 3) control (without insecticide application). The experiment was installed in a completely randomized design, with 15 replications, using leaf number 4 as samples. The parameters analyzed were number of aphids at 3 and 9 months after insecticide application and the number of leaflets/leaves with aphids at 26 months after application. The means were compared by the F and Tukey test at 5% probability level. All data were transformed into a log (x + 1). The aphid number and the number of leaflets per leaf infested with the aphid was higher in the control treatment. Thus, the application of imidacloprid via injection provided protection to coconut plants to the palm aphid, C. lataniae, until 26 months.